Kategori Fatis Bahasa Minangkabau dalam Kaba Gadih Rantih Karya Sjamsudin St. Radjo Endah - Ilmi, Febbi Imrahatul; Agustina, Agustina; Basri, Irfani (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
This research is aimed to describe phatic category of Minangkabau language from its form and usage function in that kaba Si Gadih Ranti. This research uses qualitative research with descriptive method. Data of this research is collected with the collecting technique by reading and understanding the data. Analyzing data technique in this research is done by inventing the described data, classifying data and analyzing it based on the research aim and making the summary. Based on the analyzed data, it can be concluded the invention from the research. They are: first, from the phatic form in Kaba Si Gadih Ranti found that there are four forms: (1) phatic particle, lah, pun, koh: (2) phatic blending: iyolah, disiko, hanyo lai, iyo juo (3) phatic word :iyo, garan, nantun, bana, malah, iko, nangko: and (4) phatic phrase: birawari, adok kapado, lorong kapado. Second, from its function in Kaba Si Gadih Ranti found that there are five phatic function, (1) emphasize, (2) separate, (3) strengthen, (4) convince, and (5) start the new paragraph of the story.